Role of Vitamin D3 Supplementation in the Treatment of Dry Eye Syndrome: Doi: 10.36351/pjo.v40i2.1766 - Kanwal, Bushra; Kiran, Ayesha; Muhammad Junaid Iqbal; Khalil, Iqra; Maryam, Aghna (Pakistan Journal of Ophthalmology, 2024)
Purpose: The aim of this study was to evaluate the role of vitamin D3 supplementation in treating non-Sjogren dry eye (NSDE) patients compared to the conventional treatment with artificial tears. Study Design: Non-randomized controlled Trial. Place and duration of study: Rural Health Centre (RHC) Buchaal Kalan from September 2021 to July 2022 Methods: This study allocated 108 patients with NSDE and hypovitaminosis D via two-arm parallel assignment. The sample was divided into two groups by non-probability purposive sampling. Group 1 received conventional treatment as artificial tears 4 times/day and group 2 was given oral vitamin D3 supplementation of 6000 IU daily along with artificial tears for a period of 90 days. The impact of oral vitamin D3 supplementation on NSDE was assessed by comparing means of ocular parameters of both groups over time. Tear break-up time (TBUT) in seconds and Schirmer’s test (ST) score in millimeters were primary outcome measures. The ocular surface disease index (OSDI) score and numerical pain rating scale (NPRS) were secondary outcome measures. Results: The mean age of patients in group 1 and group 2 was 34.98±8.64 and 34.87±8.79 respectively. Similarly, the mean serum 25 (OH) D level was 15.03±3.27 in group 1 and 14.93±3.26 in group 2. Results showed that OSDI and NPRS scores were decreased in both groups, however, TBUT and ST scores were improved in group 2. Conclusion: Oral vitamin D3 supplementation may serve as a new treatment option for NSDE patients having hypovitaminosis D.